2014
DOI: 10.1074/jbc.m114.587493
|View full text |Cite
|
Sign up to set email alerts
|

MDM2 Regulates Hypoxic Hypoxia-inducible Factor 1α Stability in an E3 Ligase, Proteasome, and PTEN-Phosphatidylinositol 3-Kinase-AKT-dependent Manner

Abstract: Background: HIF1␣ is degraded under normoxic conditions by VHL. Degradation under hypoxia is poorly understood. Results: HIF1␣ is degraded under hypoxia via 26 S proteasome; MDM2/E3 ligase, under the control of PI3K, mediates the hypoxic degradation of HIF1␣ in glioma systems. Conclusion: MDM2 action on HIF1␣ under hypoxia is controlled by PI3K signaling. Significance: Results reveal a mechanism controlling hypoxic HIF1␣ degradation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
69
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 48 publications
6
69
0
1
Order By: Relevance
“…3a, b). We recently published that HIF-1α can be degraded under hypoxic conditions via the 26S proteasome and that MDM2, a E3 ligase is necessary for the hypoxic degradation of HIF-1α [34]. Similar to this report, we observed that MDM2 is mediating the degradation of HIF-2α in VHL-null 786-0 cells in proteasome and PI-3K-dependent manner (Fig.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…3a, b). We recently published that HIF-1α can be degraded under hypoxic conditions via the 26S proteasome and that MDM2, a E3 ligase is necessary for the hypoxic degradation of HIF-1α [34]. Similar to this report, we observed that MDM2 is mediating the degradation of HIF-2α in VHL-null 786-0 cells in proteasome and PI-3K-dependent manner (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…The observation that HIF-α can be degraded under hypoxic conditions in PI-3K-dependent manner suggested the involvement of a potential E3 ligase in proteasome-dependent degradation. In a recently published work from our laboratory, we reported that MDM2, whose transport between the cytoplasm and nucleus is regulated by PI-3K/AKT, is the E3 ligase controlling HIFdegradation [34]. In order to test whether this hypothesis is true in VHL-null 786-0 cells, phosphorylation site mutants of MDM2 which regulate subcellular localization of this protein were employed.…”
Section: Sf1126 Regulates Mdm2-induced Hypoxic Degradation Of Hif-1α/mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, HIF-1a protects p53 from MDM2-dependent nuclear export and ubiquitylation [19]. That the interaction between MDM2 and HIF-1a is p53-independent has been further confirmed in p53 À/À and p53 +/+ cells, but the data have yielded contradicting interpretations: opposing and equally represented factions support MDM2-dependent degradation [8,12,18,20,21] or MDM2-dependent upregulation [16,22,23] of HIF-1a. It appears extremely complex to explain the current contradictions regarding the role of MDM2.…”
mentioning
confidence: 99%
“…Since p53 mutations are observed in approximately 10% of AML samples, and since this mutation is associated with devastating prognosis [105], it would be of great interest to determine whether this mutation contributes to increased HIF-1α accumulation in AML. Given the fact that MDM2 is an E3 ligase for HIF-1α [106, 107], p53 mutations may increase HIF-1α levels by decreasing MDM2. Fourth, NPM1 is mutated in 30–40% of AML samples that have a normal karyotype [108, 109].…”
Section: Epigenetic and Genetic Mechanisms For Hif Activities Under Nmentioning
confidence: 99%